2 - Shared Governance and Leadership in African Universities: Experiences from Mzuzu University, Malawi, and Amoud University, Somaliland: 10.4314/ad.v30i1.22211 - Nur-Awaleh , Somaliland MohamedA.; Mtegha , Dorothy M. (Africa Development, 2005)
This paper examines the application of shared governance structure and leadership styles in African Universities, specifically at Mzuzu university in Malawi and Amud University in Somaliland. First, a brief background about Mzuzu and Amoud Universities, and their governance structure will be presented. This is followed with the description and analysis of data on teamwork, job satisfaction, shared decision-making at Mzuzu and Amoud universities. Finally, this paper will provide recommendations for African universities who are faced with similar problems of shared governance with valuable data regarding governance and leadership, and provide information about the ways in which universities governance can be modified to increase the success of higher education institutions.